Hybrid supercapacitor with nano-TiP2O7 as intercalation electrode - Aravindan, Vanchiappan (2011)
Nano-size (≤ 100 nm) TiP2O7 is prepared by the urea assisted combustion synthesis, at 450 oC and 900 oC. The compound is characterized by powder X-ray diffraction, Rietveld refinement, high resolution transmission electron microscopy and surface area methods. Lithium cycling properties by way of galvanostaic cycling and cyclic voltammetry (CV) showed a reversible and stable capacity of 60 (± 3) mAh g–1 (0.5 mole of Li) up to 100 cycles, when cycled at 15 mA g–1 between 2-3.5 V vs. Li. Non-aqueous hybrid supercapacitor, TiP2O7 (as anode) and activated carbon (AC) (as cathode) has been studied by galvanostatic cycling and CV in the range, 0-3 V at 31 mA g–1 and exhibited a specific discharge capacitance of 29 (± 1) F g–1stable in the range, 100-500 cycles. The Ragone plot shows a deliverable maximum of 13 Wh kg–1 and 371 W kg–1 energy and power density, respectively.